In vivo and in vitro regulation of plasminogen activator inhibitor type-1 - Keeton, Mark R (Department of Clinical Laboratory Sciences, 2024)
The human leukaemic cell line, K562 can be induced to differentiate along the megakaryoblastic pathway by the addition of phorbol myristate acetate and, during this process, the cells switch from producing a mixture of active tissue plasminogen activator (t-PA) and urokinase (u-PA) to producing active u-PA alone. I performed a series of experiments designed to examine the mechanism of down regulation of t-PA activity that occurred with differentiation. The results of these experiments showed that, in the K562 system at least, differentiation-linked changes in t-PA activity are incidental to plasminogen activator inhibitor type-1 (PAl-1) synthesis and release and that the inhibitor is a critical regulatory protein in this model system. I therefore chose to study the regulation of PAl-1 both in vitro and in vivo. To perform the in vitro regulation studies, DNA constructs derived from the PAl-1 promoter and 5' flanking sequence were cloned upstream of a luciferase reporter gene. These constructs were transfected into human hepatoma cells, the cells treated with TGFB for 24 hours after which luciferase activity was measured as a function of promoter activity. The active regions were also analyzed by gel retardation to investigate the transcription factors that bound to these regions. The functional data taken together with the DNA binding data supported the hypothesis that the response of the PAl-1 promoter to TGFP was mediated by two conserved regions of the promoter and 5' flanking sequence, both of which contain DNA sequences with homology to the activator protein-1 (AP-1) consensus sequence. I then focused on a single region from the PAl-1 5' flanking region in an attempt to define the role of the AP-1-like sites in the TGFB response. The direct response of this region to AP-1 was assessed by co-transfection of plasmids containing the genes for c-fos and c-jun together with the PAl-1 /reporter constructs. My data indicates that the full TGFB response of this region of the PAl-1 promoter is dependent on the interaction of two distinct binding sites. Although the first site has homology to the AP-1 site, it does not appear to bind AP-1 . While this site does not appear to be essential, it is required for the full TGFB response of this region. The second site, located 5' to the AP-1 site, appears to be critical in the TGFB response. This site is 15bp in length and contains a motif that is present in both active regions of the PAl-1 promoter. This novel sequence does not appear to correspond to any previously described transcription factor binding site and may represent a new and specific binding site which is critical for a strong TGFB response. My in vivo studies were aimed at determining the sites of PAl-1 synthesis in the normal mouse and then examining how these changed during diseases known to have a predisposition to thrombosis. I used an acute phase model in which mice were injected with endotoxin. In situ hybridization and immunhistochemical analysis revealed that the normal animal produced a low level of PAl-1 and this was confined primarily to smooth muscles cells of the vessel wall. In contrast, following injection with endotoxin, there was a large increase in PAl-1 synthesis by vascular endothelium throughout the animal. I also studied the distribution of PAl-1 in a more chronic model of renal disease. This study of murine lupus nephritis (LN) demonstrated a number of unique features about the expression of PAl-1 in vivo. First of all, I found the chronic expression of PAl-1 in a disease in which coagulation is a prominent feature. I showed that many cell types express PAl-1, a fact that had been suggested by in vitro studies but not previously demonstrated in vivo. Finally, I demonstrated that the PAl-1 expression is localised to sites of active disease. All of this data is suggestive of a role for this potent anti-fibrinolytic molecule in the ongoing pathology of LN.